Medicine supply chain model for an integrated healthcare system with uncertain product complaints - Imran, Muhammad; Kang, Changwook; Babar Ramzan, Muhammad (Journal of manufacturing systems, 2018)
•A multi-objective medicine supply chain model with uncertain product complaints.•Optimization of business triade (Time, quality and cost).•Measurement of quality includes uncertain complaints of product to manufacturer.•Modified interactive multi-objective fuzzy programming method.•A numerical example of supply chain for an integrated network of healthcare system. To date, multi-period optimization using modified interactive multi-objective fuzzy programming for an uncertain number of product complaints in the medicine supply chain, has not been sufficiently reported in the literature. Therefore, the aim of this paper is to formulate and optimize a multi-period, multi-objective medicine supply chain model for an integrated healthcare system. It considers an uncertain number of medicine complaints received by manufacturers. The multi-objectives are time, quality and cost and their combination is called the business triad. This research comprises three steps. Firstly, the formulation of a mathematical model for the business triad. Secondly, the modified interactive multi-objective fuzzy programming has been suggested for the optimization of business triad. The proposed approach uses fuzzy linguistic variables and a triangular membership function that integrates expert opinion along with their experience. Finally, a numerical example is used to elaborate the practical significance of the model. The results of the numerical example showed a 31.95% satisfaction level for the cost, 41.99% satisfaction for the time, and 92.90% satisfaction for the quality of the medicines. This supply chain model assists decision makers in the healthcare systems to procure medicines with the required satisfaction level in terms of quality, time, and cost.